Web-based multimedia courseware for learning alphabet using alphabet principles for preschool / Anas Azlan - Anas, Azlan (2007)
This project considers the problem in reading capabihties among Malaysian children. Far too many children cannot read properly and having problem to learn other things due to lack of reading ability. The aim of this project is to develop a prototype web-based multimedia courseware for language learning using the Alphabetic Principles (AP) as the teaching method. Two areas of AP shown to be most important in teaching beginning readers are phonemic awareness and phonics or phonological awareness. The AP approach will be applied in the courseware and the contents will be dehvered using sounds, images and animations to help the children learn easier and more interesting. The core aspect of this project is delivering the Alphabetic Principles teaching instructions using Flash based user interface. Therefore, the development of the interface using Flash is very important in this project.